ChemInform Abstract: Rhodium(II)‐Catalyzed Regioselective Carbenoid Insertion Reaction of Simple Indoles with N‐Sulfonyltriazoles: A Rapid Access to Tryptamine Vinylogues. Issue 23 (May 2016) - Huang, Jiapian; Yang, Yi; Chen, Zhiyuan
Abstract: The rhodium‐catalyzed nitrogen extrusion from triazoles gives reactive rhodium(II) aza‐vinylcarbenes, which react with indoles to form predominantly Z‐isomers of tryptamine vinylogues.